Toxicity and Bioaccumulation of Copper in Phaeodactylum tricornutum Under Different Macronutrient Conditions - Zhou, Beibei; Zou, Yue; Ma, Jie; Li, Yanping; Pan, Ke (Frontiers in Marine Science, 2022)
In this study, we investigated cell physiological and biochemical responses to copper (Cu) accumulation in the marine diatom Phaeodactylum tricornutum under different nitrogen (N) and phosphorus (P) conditions. Cells with sufficient N and P (+N+P) showed the highest total Cu concentrations and displayed a higher metal-tolerance ability. In the +N+P treatments, 36.5% of dissolved Cu was adsorbed on the frustules (cell walls), 54.9% was occluded in organelles, and 8.6% was in the soluble fraction. In comparison, cells with N and/or P shortages (+N−P, −N+P, and −N−P) adsorbed 10.8–13.1% of the total Cu onto their cell walls, 74.5–80% was occluded in organelles, and 9.2–12.4% was in the soluble fraction. The Cu2+ influx on the +N+P cell wall was faster due to sufficient metal ligands on the cell walls and up-regulated metal-related transporters. A significant increase in protein content occurred under N and/or P shortages, which was accompanied by the inhibition of the antioxidative enzymatic system and cell membrane damage. Our findings indicate that N and P play an important role in both Cu adsorption (cell surface) and uptake (intracellular), and they provide multifaceted evidence of the Cu acquisition mechanism in P. tricornutum under different macronutrient conditions.